PENGEMBANGAN INSTRUMEN SIKAP ILMIAH UNTUK SISWA SEKOLAH DASAR - Dewa nyoman sudana (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to determine: (1) the stages of development of scientific attitude instruments for elementary school students. (2) the quality of the instruments developed scientific attitude in terms of validity, reliability, and validity konstruknya. Methods of data collection using questionnaires with respondents 200 elementary school students from class IV to class VI. Analysis using the statistical analysis program assisted SPPS 13 for Windows. The steps include instrument development; 1) set of constructs, which set limits on the variables to be measured, 2) determine the factors to find the elements that exist in a construct, 3) prepare a statement grains, 4) implement test instrument was developed. Judging from the quality of the instruments developed realibitas looks pretty good instrument category at 0.881 and after the instrument items were eliminated from about 36 to 15 are also still in the good category is 0.813. Based on the criteria of commonality factor extraction and rotation factors obtained four factors, number of factors extracted by the factor of as much as 4 percent of the cumulative variance is greater than 60% is 65.834%. Judging from the validation performed factor by dividing the number of respondents into two groups of parts, and then performed a factor analysis on each hemisphere of the respondents. The results showed that the factor validation valid results, each still produce a 4 factor with almost equal distribution of items. This further strengthen that 4-dimensional factor in the scientific attitude for elementary school children on an instrument that has developed a strong enough konstruknya validity. The results of the development of scientific instruments already reflect the attitude and decent results are used to measure the scientific attitude of students in elementary school